Basket case science, basket case society - Khanal, Udayaraj (Himalayan Journal of Sciences, 2006)
It is quite obvious that there is not any significant development in science in Nepal. Many people maintain that the government and politicians are fully or mainly responsible for this quandary, as for every other. But the author digs deeper to discover the underlying causes. He argues that the scientific failure happened ‘through’ the politicians, not ‘by’ them.Himalayan Journal of Sciences 1(2): 77-79, 2003The full text is of this article is available at the Himalayan Journal of Sciences website